An Emissions Trading Scheme for Australia: National and Regional Impacts1. Issue 290 (28th April 2014) - Adams, Philip D.; Parmenter, Brian R.; Verikios, George
<x xml:space="preserve">Abstract</x> Computable general equilibrium modelling in Australia is oriented towards providing inputs to the policy‐formation process, a process that requires detail. We explain how the necessary level of detail can be provided using analysis of the potential economic impacts of a carbon price on the Australian economy that operates as part of a global emissions trading scheme. The global scheme sets the price and allocation of permits across countries. We find that domestic abatement falls well short of targeted abatement, Australia's GDP is 1.1 per cent lower relative to the basecase, and some industries and regions are vulnerable to employment losses.